2009
DOI: 10.1162/evco.2009.17.1.117
|View full text |Cite
|
Sign up to set email alerts
|

Reinterpreting No Free Lunch

Abstract: Since its inception, the “No Free Lunch” theorem (NFL) has concerned the application of symmetry results rather than the symmetries themselves. In our view, the conflation of result and application obscures the simplicity, generality, and power of the symmetries involved. This paper separates result from application, focusing on and clarifying the nature of underlying symmetries. The result is a general set-theoretic version of NFL which speaks to symmetries when arbitrary domains and co-domains are involved. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…A different approach to NFL showed that the theorem also holds for arbitrary domains and co-domains [28]. In contrast, other studies [29,30] showed that the NFL theorem does not hold in continuous domains although its soft form of NFL holds in countably infinite domains.…”
Section: Discrete Vs Continuous Spacementioning
confidence: 92%
“…A different approach to NFL showed that the theorem also holds for arbitrary domains and co-domains [28]. In contrast, other studies [29,30] showed that the NFL theorem does not hold in continuous domains although its soft form of NFL holds in countably infinite domains.…”
Section: Discrete Vs Continuous Spacementioning
confidence: 92%
“…From the no-free-lunch (NFL) theorems for optimization, that have already been widely discussed from various points of view (Wolpert and Macready 1997;Köppen et al 2001;Schumacher et al 2001;Droste et al 2002;Whitley and Rowe 2008;Rowe et al 2009;Duéñez-Guzmán and Vose 2013), it is well known that the performance of all heuristic optimizers averaged over all problems is equal. Although it is generally understood that only a very small fraction of "all problems" [for a detailed discussion of what "all problems" means, see Wolpert and Macready (1997) and Schumacher et al (2001)] is of interest to anyone Toussaint 2003, 2004), it is very unfortunate that the implications of the NFL are rarely considered and discussed when novel metaheuristics are proposed.…”
Section: Background: Recent Criticisms Of Optimization Metaheuristicsmentioning
confidence: 99%
“…We begin by summarizing the basic definitions of Black Box search algorithms, following notation used in [6].…”
Section: Black Box Algorithmsmentioning
confidence: 99%